2018
DOI: 10.1016/j.sjbs.2016.09.021
|View full text |Cite
|
Sign up to set email alerts
|

The potential protective influence of flaxseed oil against renal toxicity induced by thioacetamide in rats

Abstract: The present study was aimed to evaluate the influence of flaxseed oil on renal toxicity induced by thioacetamide in male rats. The animals were distributed into four groups. Rats of the first group were served as control. Rats of the second group were exposed to thioacetamide. Rats of the third group were treated with flaxseed oil and thioacetamide. Rats of the fourth group were treated with flaxseed oil. Significant increases of blood creatinine and uric acid were observed in TAA-treated rats after three week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 46 publications
5
10
0
Order By: Relevance
“…These findings imply that FO can block the inflammatory process and oxidative stress, which are responsible for CdCl 2 -induced toxicity. These observations support the down-regulation of TNF-α mRNA expression observed in the present work and are also in agreement with previous studies [ 21 , 22 , [31] , [32] , [33] ]. For example, Hendawi et al [ 34 ], found that oral administration of FO (0.5 g/kg) inhibited thiacloprid-induced liver histopathological damage in rats by promoting antioxidant defense system, decreasing lipid peroxidation, reducing proinflammatorycytokines, and stabilizing the DNA during cell division.…”
Section: Discussionsupporting
confidence: 94%
“…These findings imply that FO can block the inflammatory process and oxidative stress, which are responsible for CdCl 2 -induced toxicity. These observations support the down-regulation of TNF-α mRNA expression observed in the present work and are also in agreement with previous studies [ 21 , 22 , [31] , [32] , [33] ]. For example, Hendawi et al [ 34 ], found that oral administration of FO (0.5 g/kg) inhibited thiacloprid-induced liver histopathological damage in rats by promoting antioxidant defense system, decreasing lipid peroxidation, reducing proinflammatorycytokines, and stabilizing the DNA during cell division.…”
Section: Discussionsupporting
confidence: 94%
“…Moneim et al showed that consumption of 1,000 mg/kg flaxseed oil in rats not only depicted no toxicity but also limit the renal cytotoxicity (Abdel Moneim et al., 2011). The other studies also confirm the potential protective influence of flaxseed oil against renal toxicity through alteration biochemical and histopathological factors (Shaikh Omar, 2018). These data confirmed the low toxicity and therapeutic potency of the mentioned oil.…”
Section: Discussionmentioning
confidence: 57%
“…This could be explained due to the presence of free radical scavengers and vitamin E contents in SL and FS which prevent hemolysis of red blood cells and lipid peroxidation (Anwar & Mohamed, 2010;El Kutry & Sopeah, 2020). Omar, 2018). Moreover, the antioxidant activity of SL and FS could inhibit and block the influence of oxidative renal damage induced by CsA (Almeer et al, 2019;Omar, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Omar, 2018). Moreover, the antioxidant activity of SL and FS could inhibit and block the influence of oxidative renal damage induced by CsA (Almeer et al, 2019;Omar, 2018). Cumulative data suggest that reactive oxygen molecules play a function as one of the postulated mechanisms for CsA nephrotoxicity (Toson et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation